2015
DOI: 10.1038/cdd.2015.8
|View full text |Cite
|
Sign up to set email alerts
|

Combined loss of the BH3-only proteins Bim and Bmf restores B-cell development and function in TACI-Ig transgenic mice

Abstract: Terminal differentiation of B cells depends on two interconnected survival pathways, elicited by the B-cell receptor (BCR) and the BAFF receptor (BAFF-R), respectively. Loss of either signaling pathway arrests B-cell development. Although BCR-dependent survival depends mainly on the activation of the v-AKT murine thymoma viral oncogene homolog 1 (AKT)/PI3-kinase network, BAFF/BAFF-R-mediated survival engages non-canonical NF-κB signaling as well as MAPK/extracellular-signal regulated kinase and AKT/PI3-kinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 54 publications
3
13
0
Order By: Relevance
“…These data suggested that inhibition of BIM and/or BMF in donor HSPCs could be a useful means to achieve superior transplantation outcome. Permanent apoptosis resistance, however, is associated with an increased risk of leukemogenesis and autoimmunity, and recipient mice transplanted with Bim −/− or Bim −/− Bmf −/− BM cells died of autoimmune kidney disease and/or lymphoma within 1 yr ( Labi et al, 2014 ; Woess et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…These data suggested that inhibition of BIM and/or BMF in donor HSPCs could be a useful means to achieve superior transplantation outcome. Permanent apoptosis resistance, however, is associated with an increased risk of leukemogenesis and autoimmunity, and recipient mice transplanted with Bim −/− or Bim −/− Bmf −/− BM cells died of autoimmune kidney disease and/or lymphoma within 1 yr ( Labi et al, 2014 ; Woess et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…S6C). In all these conditions, loss of BIM had been reported to exert anti-apoptotic activity (Oliver et al 2006;Woess et al 2015 Figure 6. Specific disruption of miR-17∼92:Bim interactions does not detectably affect B cells.…”
Section: Mir-17∼92:bim Interactions Are Essential For Lung Developmentmentioning
confidence: 98%
“…Histological evaluation of spleens from double-transgenic mice indicated reduced follicle and germinal center size. 6…”
Section: Introductionmentioning
confidence: 99%